2014
DOI: 10.1103/physreva.89.051401
|View full text |Cite
|
Sign up to set email alerts
|

Strongly driven quantum pendulum of the carbonyl sulfide molecule

Abstract: We demonstrate and analyze a strongly driven quantum pendulum in the angular motion of state-selected and laser-aligned carbonyl sulfide molecules. Raman couplings during the rising edge of a 50-ps laser pulse create a wave packet of pendular states, which propagates in the confining potential formed by the polarizability interaction between the molecule and the laser field. This wave-packet dynamics manifests itself as pronounced oscillations in the degree of alignment with a laser-intensity-dependent period.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 36 publications
1
41
1
1
Order By: Relevance
“…These experiments require pure samples delivered into a micrometer-sized interaction region, which can be achieved using electrostatic control techniques applied to cold molecular beams [19][20][21]. Moreover, these techniques also allow the dispersion of rotational states, such that the coldest molecules from a molecular beam can be selected, yielding, e. g., higher degrees of molecular one-and three-dimensional alignment and orientation [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…These experiments require pure samples delivered into a micrometer-sized interaction region, which can be achieved using electrostatic control techniques applied to cold molecular beams [19][20][21]. Moreover, these techniques also allow the dispersion of rotational states, such that the coldest molecules from a molecular beam can be selected, yielding, e. g., higher degrees of molecular one-and three-dimensional alignment and orientation [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that a degree of alignment of <cos 2 θ 2D > = 0.97 can be achieved by adiabatically laser-aligning iodobenzene molecules when an electrostatic deflector 33 is employed for selecting only the coldest molecules in the molecular beam 34 . Furthermore, it was recently demonstrated that a stretched femtosecond Ti:Sapphire laser pulse instead of a Nd:YAG laser pulse can be used to align carbonyl sulfide molecules to a very high degree 35 , which would eliminate the limitation to a 30 Hz repetition rate in our experiments because of the Nd:YAG laser. Field-free alignment methods, which would allow pumping and probing the molecules at a time when the strong alignment-laser pulse is no longer present, have also recently achieved much improved degrees of alignment 36,37 , suggesting that they may soon be a viable alternative to adiabatic laser alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Through a movable third skimmer, the molecular beam entered the spectrometer. Here, it was crossed at right angle by laser beams, where the height of the laser beams allowed to probe state-selected molecular ensembles, i. e., a practically pure rovibronicground-state sample of OCS [16,20,40].…”
Section: Methodsmentioning
confidence: 99%